The influence of discounts, live online shopping on TikTok on purchasing decisions through product quality : (Case study of @camille beauty skincare products in DKI Jakarta Province) - Mailani, Indah; Maftuchach, Viniyati; Wati, Lela Nurlaela (Privietlab, 2025)
Advancement of digital technologies, internet usage is experiencing substantial growth. Technological advancement has significantly transformed contemporary commercial systems, especially free trade facilitated by electronic platforms (e-commerce). This study seeks to examine the impact of discounts and live shopping on TikTok on the purchasing decisions for Camille Beauty skincare items, with product quality serving as a mediating variable. Data was obtained from 170 respondents residing in Jakarta using a Likert scale-based questionnaire and employing quantitative methodologies with a causality approach. Analysis was conducted employing multiple linear regression approaches with SmartPLS 4.0. The research findings indicate that discounts positively and significantly affect product quality, however negatively and significantly influence purchasing decisions. Conversely, live shopping exerts a considerable adverse effect on product quality and purchasing choices. While product quality exerts a favorable effect, its impact on purchasing decisions is minimal. Mediation research indicated that discounts and live shopping did not significantly affect purchasing decisions when mediated by product quality. This research underscores the need to preserve product quality to cultivate consumer confidence and enhance the efficacy of promotional techniques to stimulate sales.